THE POSITION OF DAUGHTERS IN BALINESE CUSTOMARY INHERITANCE SYSTEM FROM GENDER EQUALITY PERSPECTIVE - Asih, Ni Made Sumerti; Citra, Made Emy Andayani (UNISSULA, 2021)
The equality of men and women in the inheritance system is a concern in the development of Balinese customary law. Basically, Balinese indigenous people adhere to a patrilineal kinship system. As a consequence, the line is drawn from the father and the heirs are only boys, while girls can only enjoy the assets of their parents as long as they are not married. This condition certainly reduces women's access to economic rights. Whereas, the economic control is very important in life. In this research, two issues are discussed, namely the inheritance system according to Balinese customary law and the struggle for gender equality through the position of women as heirs. Decree of the Pesamuhan Agung Majelis Utama Desa Pakraman Bali Number 01 / KEP / PSM-3 / MDP Bali / X / 2010, dated October 15, 2010 provides opportunities for girls to become heirs with limited provisions. Even so, the position of women as heirs in Balinese customary law is still difficult to be implemented. This is due to a very strong patriarchal culture that places men in higher power relations.Â